MODEL PEMBELAJARAN BERBASIS PROYEK (PjBL) TERINTEGRASI STEM UNTUK MENINGKATKAN LITERASI SAINS SISWA MTS PADA MATERI SISTEM ORGANISASI KEHIDUPAN - Esthy Srigati (Wawasan: Jurnal Kediklatan Balai Diklat Keagamaan Jakarta, 2020)
This research aims to study the implementation of the PjBL-STEM strategy to increasing scientific literacy in students at MTsN 28 Jakarta. The study population was students of class VII MTs Negeri 28 East Jakarta in the 2018/2019 academic year with a sample of 2 similar classes each of 32 students. This research is exploratory using multi methods, namely case studies and experiments. Researchers conducted lesson in the experimental class using the PjBL-STEM strategy in life systems organization curriculum subject. The lesson was observed in the implementation process, student responses and measure scientific literacy level. To ensure the functioning of this strategy in improving scientific literacy, researcher measured scientific literacy level in the control class. The research used observation, survey and test to collect data using observation sheets, questionnaires and test items. The data were processed using descriptive statistics and t-test. Research shows that the implementation and response to the implementation of the PjBL-STEM strategy is categorized as good. Students' scientific literacy in the knowledge aspect of the experimental class was better than the control class, not significantly different in the aspect of identifying scientific issues, while in the aspect of using scientific evidence the experimental class was superior to that of the control class. The experimental class showed a positive response and was happy with the implementation of PjBL-STEM. The research recommends science teacher to use PjBL-STEM strategy in a certain topic and condition.